Science Teachers' Technical Difficulties in Using Physical Computing and the Internet of Things Into School Science Inquiry - Ga, Seok-Hyun; Park, Changmi; Cha, Hyun-Jung; Kim, Chan-Jong (IEEE transactions on learning technologies, 2024)
Data collection is crucial in securing evidence to support students' arguments during scientific inquiries. However, due to the high costs associated with equipping schools with various measurement devices, students are limited in the scope of their scientific inquiry. Arduino can be proposed as a solution to the lack of measurement devices in schools. With Arduino, students can create various measurement devices by connecting different sensors, customize these devices to suit their inquiries, and implement remote sensing using the Internet of Things. However, even when promising new technology serves as a beneficial tool for teaching and learning, its successful integration into the educational system can be challenging if teachers struggle to use it. Technical issues often discourage teachers from incorporating potentially valuable technologies into their classrooms. This article examined the adoption of Arduino in three different cases involving teachers from various educational institutions: a gifted education center, an autonomous club activity in a middle school, and a local community center. We identified four major difficulties: 1) selection of appropriate technologies; 2) credibility issues with information from the Internet; 3) technical complexity due to the intervention of multiple variables; and 4) compliance issues with related acts and regulations. We described each of the technical challenges that teachers faced, in detail, and how they dealt with them. Finally, we discussed suggestions for reducing the barriers to Arduino use for teachers and proposed areas for further research.